Information needs of customer care centres managers in Singapore banking industry. - Lim, Cheng Keong. (2008)
This study elicits the information needs of Customer Care Centers managers in the Singapore banking industry. Specifically, it attempts to understand the roles of information needed and its significance in the Customer Care Centers; it identifies the various categories of information that are gathered for their work and the actual information sources acquired and used.